Educational inequality in adult mortality: an assessment with death certificate data from Michigan. - Christenson, Bruce A.; Johnson, Nan E. (Demography, 1995)
A study was conducted to evaluate the quality of data on education from death certificates and to examine educational differences in mortality rates. Results revealed that the relative differences in mortality rates between educational levels decline with age at the same rate for all sex and race categories. Women were found to gain a slightly greater reduction in mortality than did men by reaching the secondary-education level but gained a modestly smaller reduction by advancing beyond this level. By moving from the secondary to the postsecondary level, blacks demonstrated a reduction in predicted mortality rates comparable to whites' rates but experienced less reduction than did whites by moving from the primary to the secondary level. Therefore, the secular decline in mortality rates that usually accompanies historical improvements in education could actually be related to an increase in the relative differences between blacks' and whites' mortality.